Percutaneous Coronary Intervention in a Patient with Right-Sided Heart: Invert the Views? - Miguel López Hidalgo; Risshi D. Rampersad (Case Reports in Cardiology)
Situs inversus totalis considered a malposition syndrome is a very rare condition, occurring in 1 : 8000 births, usually without associated structural congenital heart disease. The diagnosis is often incidental as in this case, which presented with an acute coronary syndrome as a manifestationof multivessel coronary artery disease. Here, we present the challenges encountered during the diagnosis and management of this entity via percutaneous intervention.